PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS PROBLEM SOLVING PADA MATERI SISTEM EKSKRESI MANUSIA UNTUK SISWA SEKOLAH MENENGAH ATAS (SMA) - Anita, Pitri; Sudirman, Sudirman; Fifendy, Mades (STKIP PGRI Sumbar, 2013)
ABSTRACTStudent Worksheet is one sheet containing materials in which there is a summary of the material that is accompanied by a collection of exercises . With the LKS students are expected to understand the description of the subject matter provided by the teacher. Based on observations and interviews that have been conducted in SMA PGRI 3 Padang that in the second semester junior class XI using teaching materials such as worksheets, worksheets used in schools does not meet the learning objectives that are developed by teachers and worksheets used in schools only contains only a summary of the material and not equipped with an image.This research aims to generate worksheets based Problem Solving biological material system ekskresi of human on a valid and practical . Type of research is the development of the procedural model that aims to produce a product, the product is developed using 3 - D stage of Four models define phase , design , and develop .Research subjects of 5 people validator and 20 students. The research data is the primary data were analyzed by descriptive analysis. The result is the value obtained validity by faculty and teachers of 88,14%, while the value of the practicalities of 87,22% by teachers and by students of the value of the practicalities of 86,45% . It can be concluded that the BLM has produced a valid and practical .